Renal Carcinoma Is Associated With Increased Risk of Coronavirus Infections - Tripathi, Satyendra C.; Deshmukh, Vishwajit; Creighton, Chad J.; Patil, Ashlesh (Frontiers in Molecular Biosciences, 2020)
Background: The current COVID-19 pandemic has affected most severely people with old age, or with comorbidities like hypertension, diabetes mellitus, and cancer. Cancer patients are twice more likely to contract the disease because of the malignancy or treatment-related immunosuppression; hence identification of the vulnerable population among these patients is essential. Method: We took a bioinformatics approach to analyze the gene and protein expression data of these coronavirus receptors (DPP4, ANPEP, ENPEP, TMPRSS2) in human normal and cancer tissues of multiple organs including the brain, liver, kidney, heart, lung, skin, GI tract, pancreas, endocrine tissues, and the reproductive organs. RNA-Seq data from The Cancer Genome Atlas (TCGA) and GTeX databases were used for extensive profiling analysis of these receptors across 9736 tumors and 8587 normal tissues comparing coronavirus receptors. Protein expression from immunohistochemistry data was assessed from The Human Protein Atlas database including 144 samples, corresponding to 48 different normal human tissue types and 432 tumor samples from 216 different cancer patients. The correlations between immune cell infiltration, chemokine, and cytokines were investigated via Tumor Immune Estimation Resource (TIMER) and TCGA. Result: We found that among all, renal tumor and normal tissues exhibited increased levels of ACE2, DPP4, ANPEP, and ENPEP. Our results revealed that TMPRSS2 may not be the co-receptor for coronavirus infection in renal carcinoma patients. The other receptors DPP4, ANPEP, and ENPEP may act as the compensatory receptor proteins to help ACE2. The receptors’ expression levels were variable in different tumor stage, molecular and immune subtypes of renal carcinoma. Intriguingly, in clear cell renal cell carcinomas, coronavirus receptors were associated with high immune infiltration, markers of immunosuppression, and T cell exhaustion. Conclusion: Our study indicates that CoV receptors may play an important role in modulating the immune infiltrate and hence cellular immunity in renal carcinoma. As our current knowledge of pathogenic mechanisms will improve, it may help us in designing focused therapeutic approaches.